Normothermic versus hypothermic cardiopulmonary bypass in low-risk paediatric heart surgery: a randomised controlled trial. Issue 6 (15th October 2018) - Caputo, Massimo; Pike, Katie; Baos, Sarah; Sheehan, Karen; Selway, Kathleen; Ellis, Lucy; Stoica, Serban; Parry, Andrew; Clayton, Gemma; Culliford, Lucy; Angelini, Gianni D; Pandey, Ragini; et al.
Abstract : Objective: To compare normothermic (35°C–36°C) versus hypothermic (28°C) cardiopulmonary bypass (CPB) in paediatric patients undergoing open heart surgery to test the hypothesis that normothermic CPB perfusion maintains the functional integrity of major organ systems leading to faster recovery. Methods: Two single-centre, randomised controlled trials (known as Thermic-1 and Thermic-2, respectively) were carried out to compare the effectiveness and acceptability of normothermic versus hypothermic CPB in children with congenital heart disease undergoing open heart surgery. In both studies, the co-primary clinical outcomes were duration of inotropic support, intubation time and postoperative hospital stay. Results: In total, 200 participants were recruited; 59 to the Thermic-1 study and 141 to the Thermic-2 study. 98 patients received normothermic CPB and 102 patients received hypothermic CPB. There were no significant differences between the treatment groups for any of the co-primary outcomes: inotrope duration HR=1.01, 95% CI (0.72 to 1.41); intubation time HR=1.14, 95% CI (0.86 to 1.51); postoperative hospital stay HR=1.06, 95% CI (0.80 to 1.40). Differences favouring normothermia were found in urea nitrogen at 2 days geometric mean ratio (GMR)=0.86 95% CI (0.77 to 0.97); serum creatinine at 3 days GMR=0.89, 95% CI (0.81 to 0.98); urinary albumin at 48 hours GMR=0.32, 95% CI (0.14 to 0.74) and neutrophil gelatinase-associated lipocalin at 4 hours GMR=0.47, 95% CI (0.22 to 1.02), but not at other postoperative time points. Conclusions: Normothermic CPB is as safe and effective as hypothermic CPB and can be routinely adopted as a perfusion strategy in low-risk infants and children undergoing open heart surgery. Trial registration number: ISRCTN93129502 .